OUTCOMES IN PRIMARY UNCOMPLICATED RHEGMATOGENOUS RETINAL DETACHMENT REPAIR USING PARS PLANA VITRECTOMY WITH OR WITHOUT SCLERAL BUCKLE. Issue 6 (June 2022) - Hébert, Mélanie; You, Eunice; Garneau, Jérôme; Qi, Susan Ruyu; Bourgault, Serge; Caissie, Mathieu; Tourville, Éric; Dirani, Ali
Abstract : Supplemental Digital Content is Available in the Text. PPV and PPV-SB confer similar single surgery anatomic success in primary uncomplicated rhegmatogenous retinal detachment. PPV is associated with better visual acuity at follow-up than PPV-SB. These results were also confirmed in a propensity-matched cohort of patients. Abstract : Purpose: To compare outcomes after primary uncomplicated rhegmatogenous retinal detachment repair using pars plana vitrectomy (PPV) or PPV with scleral buckle (PPV-SB). Methods: This is a retrospective cohort study with propensity score analysis in a single tertiary care center between 2014 and 2018 comparing patients with primary uncomplicated rhegmatogenous retinal detachment repaired using PPV only or PPV-SB (full cohort: n = 1, 516, propensity-matched cohort: n = 908). The primary outcome was single surgery anatomic success, whereas secondary outcomes were 3-month and final pinhole visual acuity in logarithm of the minimum angle of resolution and final retina status. Results: In the full cohort, single surgery anatomic success was achieved in 745 (91%) PPV patients versus 623 (89%) PPV-SB patients ( P = 0.13). This was 390 (92%) versus 314 (88%) in phakic patients ( P = 0.06) compared with 353 (91%) versus 301 (90%) in pseudophakic patients ( P = 0.79), respectively. After matching, single surgery anatomic success was achieved in 424 (93%) PPV patients versus 412 (91%) PPV-SB patients ( P = 0.14). Median pinhole visual acuity after PPV was better at 3 months (PPV: 20/40 vs. PPV-SB: 20/50; both cohorts: P < 0.001) and final follow-up (PPV: 20/29 vs. PPV-SB: 20/38; full cohort: P < 0.001 and PPV: 20/29 vs. PPV-SB: 20/36; matched cohort: P < 0.001). Conclusion: Addition of scleral buckle does not significantly change the rate of single surgery anatomic success compared with PPV only in primary uncomplicated rhegmatogenous retinal detachment. It is also associated with worse pinhole visual acuity at follow-up.